2016
DOI: 10.1038/ejcn.2016.69
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil- and soy oil-based lipid emulsions in neonatal parenteral nutrition: a systematic review and meta-analysis

Abstract: Both FBLs and SBLs are beneficial for neonatal PN. FBLs reduce cholestasis, and SBLs reduce the duration of respiratory support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
2
9
1
Order By: Relevance
“…This systematic review is the first to fully explore the effects that various LEs have on a comprehensive range of growth, development, laboratory and clinical outcomes in paediatric patients ranging from preterm infants to children < years of age. The majority of studies did not find significant differences between the use of different LEs and growth, liver enzymes, plasma triglycerides, oxidative stress, blood parameters and inflammatory markers, which is consistent with the findings of four previous systematic reviews investigating the safety and possible beneficial effects of different LEs in preterm infants (n=3) and children (n=1) [8][9][10][11].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This systematic review is the first to fully explore the effects that various LEs have on a comprehensive range of growth, development, laboratory and clinical outcomes in paediatric patients ranging from preterm infants to children < years of age. The majority of studies did not find significant differences between the use of different LEs and growth, liver enzymes, plasma triglycerides, oxidative stress, blood parameters and inflammatory markers, which is consistent with the findings of four previous systematic reviews investigating the safety and possible beneficial effects of different LEs in preterm infants (n=3) and children (n=1) [8][9][10][11].…”
Section: Discussionsupporting
confidence: 88%
“…In terms of the effects of LEs on morbidity outcomes, one study showed a potential benefit of fish oil-containing blends on the incidence of cholestasis [31]. This supports the findings of the systematic review of Kotiya et al, who found significantly lowered incidence of cholestasis with fish oil blends vs soybean oil or soybean oil/olive oil blends in premature and low birth weight neonates [11]. This may in part be due to the lower concentrations of phytosterols present in fish oil blends compared with predominantly soybean oil based LEs, high levels of which have been linked with PN-associated cholestasis [51].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, when data is grouped for meta-analyses that have stringent exclusion criteria MO-FE has failed to show a positive effect on treatment for PNAC [57,58]. Other meta-analysis that include less stringent inclusion criteria have found a significant positive effect with MO-FE [59,60]. In the most recent Cochrane meta-analysis, eleven studies were analyzed comparing MO-FE vs. SO-LE in infants without surgical or preexisting conditions on the efficacy of cholestasis prevention [58].…”
Section: Clinical Outcomes With Mixed Oil-based Lipid Emulsionsmentioning
confidence: 99%